2012
DOI: 10.1002/adsc.201100765
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radical Promotes the Direct Iodination of Aromatic Compounds with Iodine in Water: A Combined Experimental and Theoretical Study

Abstract: It is still a challenge to develop green, simple and effective approaches to prepare aromatic iodides. Herein, a novel and green strategy for the direct mono-iodination of aromatic compounds starting with molecular iodine has been developed. The strategy uses ceria nanocrystals to decompose hydro-gen peroxide, giving hydroxyl radicals which are demonstrated experimentally and computationally to be crucial to promote the iodinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Further EPR analysis revealed that a pH decrease lead to an increase of the EPR response which correlates with the amount of OH radicals. The pH required for oxidative iodination is lower than for bromination (pH ≤ 3.0 vs pH ≤ 7.0). For pH values ≥6.0 only hydroxylated rather than iodinated products (e.g., for benzene) were formed.…”
Section: Transition Metal Oxides As Heterogeneous Hpo/hg‐like Nanozymesmentioning
confidence: 98%
See 4 more Smart Citations
“…Further EPR analysis revealed that a pH decrease lead to an increase of the EPR response which correlates with the amount of OH radicals. The pH required for oxidative iodination is lower than for bromination (pH ≤ 3.0 vs pH ≤ 7.0). For pH values ≥6.0 only hydroxylated rather than iodinated products (e.g., for benzene) were formed.…”
Section: Transition Metal Oxides As Heterogeneous Hpo/hg‐like Nanozymesmentioning
confidence: 98%
“…The pH required for oxidative iodination is lower than for bromination (pH ≤ 3.0 vs pH ≤ 7.0). For pH values ≥6.0 only hydroxylated rather than iodinated products (e.g., for benzene) were formed. Computational studies suggested a stepwise oxidation of one iodine molecule (I 2 ) to two HOI molecules with four different iodine compounds and iodites (I + ) involved in the actual oxidative iodination step.…”
Section: Transition Metal Oxides As Heterogeneous Hpo/hg‐like Nanozymesmentioning
confidence: 98%
See 3 more Smart Citations